Implementación del sistema educativo en el establecimiento carcelario de Bogotá La Modelo : estudio de caso (2016)
The purpose of Colombian penitentiary and prison establishments is not to punish, but to reintegrate into society, primarily through education. The objective of the study was to understand how the current Model for Education in Prisons and Penitentiaries was implemented in a institution. An exploratory case study was carried out, in which the theoretical elements of the model were compared to the methodology and social aspects governing its implementation. The results led to the creation of a framework to understand the above process and a critical reflection on the hypotheses of the model and its implementation.